Meningkatkan Penjualan UMKM Binaan Program Jabar Juara Kota Depok Melalui Optimalisasi Target Market - Ade Ridwan; Anisa Marfuah; Said Mustofa; Setiadi Santoso; Juhaeri; Sachro (Jurnal Pengabdian Masyarakat Madani, 2022)
This service is entitled Increasing Sales of MSMEs Guided by the West Java Champion Program in Depok City through Optimizing Target Markets. The general purpose of this community service activity is to provide training and practical knowledge of marketing management science by using appropriate segmenting, targeting, and positioning techniques for use by MSMEs in marketing their products. The method used is direct material delivery as well as simulations and discussions regarding marketing management and re-targeting MSME products during a pandemic which is closely related to new normal conditions in the development of Micro, Small, and Medium Enterprises that have an impact on people's welfare. This PKM activity is very useful for MSME actors in the West Java Champion Development Program, Depok City, who are helped in opening additional insights and knowledge in marketing their products effectively and efficiently. PKM participants who are members of the West Java Champion MSME fostered program, Depok City, have known and understood the right techniques in implementing Segmenting, Targeting, and Positioning strategies in an effort to market and sell their products to consumers.